Microstructural characteristics of naturally formed hardpan capping sulfidic copper-lead-zinc tailings. (November 2018) - Liu, Yunjia; Wu, Songlin; Nguyen, Tuan A.H.; Southam, Gordon; Chan, Ting-Shan; Lu, Ying-Rui; Huang, Longbin
Abstract: A massive and dense textured layer (ca. 35–50 cm thick) of hardpan was uncovered at the top layer, which capped the unweathered sulfidic Cu-Pb-Zn tailings in depth and physically supported gravelly soil root zones sustaining native vegetation for more than a decade. For the purpose of understanding functional roles of the hardpan layer in the cover profile, the present study has characterized the microstructures of the hardpan profile at different depth compared with the tailings underneath the hardpans. A suit of microspectroscopic technologies was deployed to examine the hardpan samples, including field emission-scanning electron microscopy coupled with energy dispersive spectroscopy (FE-SEM-EDS), X-ray diffraction (XRD) and synchrotron-based X-ray absorption fine structure spectroscopy (XAFS). The XRD and Fe K-edge XAFS analysis revealed that pyrite in the tailings had been largely oxidised, while goethite and ferrihydrite had extensively accumulated in the hardpan. The percentage of Fe-phyllosilicates ( e.g., biotite and illite) decreased within the hardpan profile compared to the unweathered tailings beneath the hardpan. The FE-SEM-EDS analysis showed that the fine-grained Ca-sulfate (possibly gypsum) evaporites appeared as platelet-shaped that deposited around pyrite, dolomite, and crystalline gypsum particles, while Fe-Si gels exhibited a needle-like texture that aggregated minerals together and produced contiguous coating on pyrite surfaces. These microstructural findings suggest that the weathering of pyrite and Fe-phyllosilicates coupled with dolomite dissolution may have contributed to the formation of Ca-sulfate/gypsum evaporites and Fe-Si gels. These findings have among the first to uncover the microstructure of hardpan formed at the top layer of sulfidic Cu-Pb-Zn tailings, which physically capped the unweathered tailings in depth and supported root zones and native vegetation under semi-arid climatic conditions. Graphical abstract: Image 1 Highlights: Pyrite and phyllosilicates were oxidised to goethite and ferrihydrite in the hardpans. Gypsum and Fe-Si gels were dominant cementing materials. Two cementing materials displayed distinct microstructures at nanometre scale. Fe-Si gels immobilised heavy metals and lowered environmental risks.